2014
DOI: 10.1007/s00431-014-2441-0
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin vs ibuprofen: comparison of efficacy in the setting of conservative therapeutic approach

Abstract: Indomethacin was more efficacious for ductal closure although did not impact outcomes. Use of staging schema may help understand 'need to treat' and refine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Considering observational studies, all 24 studies had a cohort design. Based on the Newcastle-Ottawa Quality Assessment Scale for this type of study design, 12 studies obtained a score of 9 out of [79-81, 84, 89, 91, 93-95, 97, 99, 101], nine had a score of [83,85,86,88,92,96,98,100,102], two studies a score of 7 [82,87], and one a score of 6 [90] (Appendix 6).…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering observational studies, all 24 studies had a cohort design. Based on the Newcastle-Ottawa Quality Assessment Scale for this type of study design, 12 studies obtained a score of 9 out of [79-81, 84, 89, 91, 93-95, 97, 99, 101], nine had a score of [83,85,86,88,92,96,98,100,102], two studies a score of 7 [82,87], and one a score of 6 [90] (Appendix 6).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors [16,19,32,38,66]; 12 [21,43]; 13 [34,36,42,48,68,76,81,91,95,96,101]; 14 [34]; 15 [37,40];…”
Section: Author Contributionsmentioning
confidence: 99%
“…123 A comparison between indomethacin and ibuprofen showed comparable efficacy and safety. 124 Alongside with indomethacin, diclofenac potassium also is a NSAID included in the silver line of antiinflammatory drugs against SARS-CoV2 infection. 123 Recent reports showed that diclofenac potassium increases lymphocyte recruitment for the immune response against SARS-CoV2.…”
Section: Other Affordable Nsaidsmentioning
confidence: 99%
“…The use of indomethacin to relieve pain and discomfort has been compared to other NSAIDs even in past reports; for example, indomethacin has no anaesthetic properties with respect to diclofenac, 122 yet recent evidence recommends to better target COX‐2 and use panels of drugs against COVID‐19 including indomethacin, diclofenac and celecoxib 123 . A comparison between indomethacin and ibuprofen showed comparable efficacy and safety 124 …”
Section: Nsaids As the First Choice Recommended Drugs In The Covid‐19...mentioning
confidence: 99%